GEORGIAN LEGAL SCIENCE ABOUT BANK GUARANTEE - Nino Chipashvili (European Scientific Journal, ESJ, 2014)
Representation of European Union in Georgia says that, “Since 2004 trade between Georgia and European Union has been developing fast, European Union has become the main trade partner of Georgia and the share of trade with it became equal to one third of the annual trade balance [4]. Georgia was actively involved in the international commerce and bank relations. The geographic location of the country contributed to it as the short way from Asia to Europe passes through “Georgia South corridor”, as specified in the agreement of association of Georgia with European Union (AA) signed on June 27, 2014. According to the Appendix XV-A of the mentioned agreement, Georgia undertook the obligation to gradually draw its legislation nearer to the legislation of European Union and international legal instruments in the banking sphere. One of the objectives of the association agreement is integration of Georgian economy to European Union through “deep and comprehensive free trade area” (DCFTA). In this new reality bank guarantee acquires great significance, as quickly executable and strong security of performance of monetary obligations at the international market. It will perfectly facilitate this integration. This article is dedicated to the views and scientific opinions of Georgian well-known doctors and professors of law, related to the legal side of the bank guarantee that is reflected in their monographs. This article shows, according to the opinions of Georgian scientists, how ready Georgian law is for new challenges.